KEMAMPUAN MENDENGAR GOI YANG MENGANDUNG CHOUON PADA SISWA KELAS X SMA PEMBANGUNAN LABORATORIUM UNP - arif fadhilah; Hendri Zalman; Damai yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research is motivated by the difficulty of students in identifying the chouon (long vocal) found in goi (words). This study aims to determine the listening ability of students class X of laboratorium pembangunan UNP senior high school, school year 2018/2019, in listening goi containing chouon in more detail in accordance with the curriculum applied in the school. This study conducted in December 2018.This is a quantitative study with descriptive method. The population of this study is the students class X of laboratorium Pembangunan UNP senior high school, school year 2018/2019. The sample of this study is 25 students’ of class X MIA of laboratorium pembangunan UNP senior high school. Purposive sample technique used in sampling. The data in this study is the students score rest of listening ability of goi containing chouon.The study shows that the listening ability of goi containing chouon ii,uu,ei,dan ou has diverse score. The highest score of student listening ability is chouon ei with an average score of 74 and the lowest score in chouon uu with an average score of 40. In general, students’ listening ability is still in bad qualification and still in the passive-receptive rather than active-productive stage. It shows that students’ listening ability is only a knowledge not an ability.                                                                                               Keywords : ability, listening, goi, chouon, purposive sample.